The Impact of ICT on Economic Development in Armenia - Movsesian, Roman; Proch, Dominik; Kováčiková, Viera; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The rapid development of information and communication technologies (ICTs) has transformed the world economy and society in recent decades. This thesis examines the case of the Armenian ICT sector, its current state, trends, and its impact on various sectors of the economy and society. The thesis also identifies the Armenian ICT sector's main challenges and opportunities. It provides evidence-based insights and recommendations for policymakers and investors to foster the development of the ICT sector and leverage its potential for economic development in Armenia.
Vedoucí práce: Dominik Proch
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses